(untitled) (Journal of the College of Basic Education, 2022)
The olive tree is one of the agricultural facts that has existed for several centuries and is one of the most important oil-producing crops in the Mediterranean basin. Its cultivation has developed in many countries of the world located between latitudes (30° and 40°) north and south of the equator. Olive cultivation was characterized as a complex agricultural system that transformed from traditional fields to dense ones, and perhaps the aim is to reduce the period of its production and reduce its costs. Many of the Arab countries produce olive oil as a result of their lack of management and production methods for part or more of the measures to reduce the impact of their waste.